What Is Wrong with a Rights-based Approach to Morality?. Issue 1 (June 2019) - Kapoor, Rajesh
There is a prominent streak of scholarship in moral and political philosophy which espouses the idea that morality is rights based. In this article, I argue that such an approach not only undermines but also operates against a range of other morally significant human relationships and attitudes such as community, solidarity, care, compassion and benevolence, which play an important role in our lives. The concept of rights is a product of historical circumstances, and it risks turning morality upside down if it encourages self-righteous claims. The notion of rights can be a constituent element of morality, but the entire moral phenomenon cannot be just rights based, and rights and duties need to remain balanced.